Pendampingan Remaja Putri dalam Deteksi Dini Pencegahan Anemia di Pondok Pesantren Nurul Falah, Kabupaten Lebak - Ayi Tansah; Ismiyati Ismiyati (Poltekita: Jurnal Pengabdian Masyarakat, 2023)
Anemia can impact of body to susceptible disease, decreasing learning activities and reducing concentration. Therefore, early detection is needed to prevent anemia in young women. This activity aims to identify knowledge about anemia and the incidence of anemia in young women. The targets for this activity were young women at the Nurul Falah Islamic Boarding School Lebak Regency.  This activity was carried out from August to October 2022. The method used in the intervention was the provision of adolescent nutrition education, Hemoglobin examination and administration of Fe tablets. During monitoring, a haemoglobin check is performed again, and the final evaluation by measuring Hb levels. The activity results showed that the health education provided successfully increased students' knowledge about anemia and its prevention. This program can be seen from the average value (mean), which was initially 46.8 to 73.6 after being given counselling. The incidence of anemia is 46.6%. However, after intervention in the form of counselling in detecting and preventing anemia and administration of Fe tablets consumed every week for two months, it became 10%. So it can be concluded that there was an increase in the score of the knowledge of young students about anemia in detecting and preventing it, and there was a decrease in the incidence of anemia in female students after accompanying the consumption of Fe tablets. It is suggested that female students will be more concerned about early detection and prevention of anemia.